(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2016)
A 4 year 4 months girl presented with marked respiratory distress, puffiness of the face and neck. She was dyspneic with a respiratory rate 53 breaths/min, subcutaneous swelling and crepitus was felt over the neck, shoulder and chest. Chest examination revealed bilateral polyphonic rhonchi and the chest radiograph showed areas of lucency over the neck and both the anterior and posterior chest walls. A diagnosis of moderate exacerbation of asthma complicated with subcutaneous emphysema was made and the patient was managed conservatively with nebulized salbutamol, steroids, oxygen and antibiotic. She made a remarkable improvement and has remained in a stable clinical condition. JCMCTA 2015 ; 26 (2) : 73 - 76